Rasionalitas Penciptaaan Alam Semesta Menurut Perspektif Islam dan Barat - mufida, farhanan atsana; Naffa, Fityatun; Febriyana, Frida; Habibah, Ummu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
The Oscillation Theory put forward by Fred Hoyle, a British astrophysicist, states that the universe experiences a repetitive cycle between expansion (Big Bang) and contraction (Big Crunch). This theory shook up scientific thought and sparked debate with the teachings of Islam, which emphasized creation as a meaningful divine act. This study aims to show that the Islamic view of the creation of the universe is more relevant and rational than the Oscillation theory in the Western perspective. This study uses a qualitative approach through the library research method to analyze the Oscillation theory in Western and Islamic perspectives, supported by the postulates of the Qur'an, especially Surah Al-Anbiya verse 30. Although the Oscillation theory provides interesting insights into the mechanisms of the universe, it tends to ignore the existence of divine purpose and control in the process of creation. Whereas in the Islamic view, creation is considered a deliberate divine action, with each element having a specific role. This research shows that the Islamic view is more relevant and able to provide a deeper understanding of the creation of the universe, so that it is not trapped in Western doctrine.